Developing The Brand Image Of Sharia Banking To Achieve Customers Equity - Widyastuti, Sri; Kartini, Dwi; Marty Oesman, Yevis; Yunizar, Yunizar (Opción, 2019)
Purpose –This research was conducted to know how the performance of integrated marketing communication and customer relation manage- ment can influence the customer of Islamic Commercial Bank in Jabo- detabek through the development of the brand image. Design/methodology/approach – This research is descriptive and verifi- cation that used a survey as the data collection method to 218 customers who have mudharabah saving account in sharia banks in Jabodetabek, Indonesia. Findings – The result of the study shows that customer equity can be achieved by the performance of integrated marketing communication and customer relationship management through the development of the brand image. Integrated marketing communication performance has a stronger influence than customer relation management performance to create customer equity. Research limitations/implications – the limitation of this research is the research area that focused in Jabodetabek, Indonesia, and the research object that focused on sharia banks. Practical implications – This research is very significant for sharia bank studies that focused on formulating the marketing communica- tion strategy and customer relationship management program, as well as the effort to build a brand image, substantial customer equity, and ultimately become the most favored bank by customers. Social implications: This research studied the customers of sharia banks in Indonesia. Indonesia has the most significant number of the muslim population in the world. This research will have implications for satisfying customers’ needs emotionally and rationally sharia bank services. Customer’s emotional needs that fulfilled for sharia banks are closely related to their religious beliefs. Rational needs met by Islamic banking service related to the speed of service, staff’s hospitality, trustworthy, and reliable services. Thus, public confidence in Islamic banking services will continue to grow. Originality/value –The result will give some point of views about sha- ria banking in Indonesia in achieving customer equity by developing a positive sharia bank image. Customer equity is produced by the custom- er lifetime value through retention in banking services, religious-mo- tive-driven customer decision, and life-goal achievement/Falah.